A influência da argamassa no desempenho acústico de paredes de vedação com blocos cerâmicos - Stradiotto, Júlia (Universidade do Vale do Rio dos Sinos, 2016)
The ABNT NBR 15575 publication generated the need to understand the performance of systems and materials employed in construction. For this article a system that is widely used in the south of Brazil was chosen with the purpose of analyzing and quantifying the acoustic performance of masonry ceramic blocks with different plaster combinations. Starting from previously conducted airborne sound insulation laboratory tests, results of three non-loadbearing wall systems were analyzed in a total of 11 compositions. The results showed that walls plastered on both sides can present up to 8 dB increases in the Rw of the analyzed samples. Furthermore, we compared results of walls with filled and unfilled vertical joints and compared the results with the mass law projection.
Keywords: Isolamento de ruído aéreo; Desempenho acústico; Alvenaria com blocos cerâmicos; Acoustic performance; Masonry walls with ceramic blocks